2008
DOI: 10.3348/kjr.2008.9.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Needle Tract Implantation after Percutaneous Interventional Procedures in Hepatocellular Carcinomas: Lessons Learned from a 10-year Experience

Abstract: Percutaneous interventional procedures under image guidance, such as biopsy, ethanol injection therapy, and radiofrequency ablation play important roles in the management of hepatocellular carcinomas. Although uncommon, the procedures may result in tumor implantation along the needle tract, which is a major delayed complication. Implanted tumors usually appear as one or a few, round or oval-shaped, enhancing nodules along the needle tract on CT, from the intraperitoneum through the intercostal or abdominal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…Additionally, three cryoprobes were inserted sequentially, and one of them was inserted into the tumor with an interposition of the normal hepatic parenchyma at a short distance, although we could not judge which needle tract was responsible for the seeding tumor because of the proximity of the three hepatic insertion sites. The possible mechanisms of tumor seeding are as follows: adherence of viable cancer cells to the needle, blood reflux along the tract, or cancer cells being forced into the tract due to increased intratumoral pressure [7]. Tumor seeding typically occurs along the needle tract, but in a few cases, occurred at a distant location in the peritoneal cavity [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, three cryoprobes were inserted sequentially, and one of them was inserted into the tumor with an interposition of the normal hepatic parenchyma at a short distance, although we could not judge which needle tract was responsible for the seeding tumor because of the proximity of the three hepatic insertion sites. The possible mechanisms of tumor seeding are as follows: adherence of viable cancer cells to the needle, blood reflux along the tract, or cancer cells being forced into the tract due to increased intratumoral pressure [7]. Tumor seeding typically occurs along the needle tract, but in a few cases, occurred at a distant location in the peritoneal cavity [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor seeding typically occurs along the needle tract, but in a few cases, occurred at a distant location in the peritoneal cavity [3,6]. Various risk factors of tumor seeding after percutaneous hepatic ablation treatments have been reported, including subcapsular location of the tumor, direct subcapsular needle insertion, number of sessions, tumor differentiation, a large needle bore, and tumor size and biopsy prior to ablation [6,7]. Wang et al showed, via multivariate analysis, that the only significant risk factor for seeding was direct subcapsular needle insertion in the cryoablation of a hepatic tumor [6].…”
Section: Discussionmentioning
confidence: 99%
“…The failure of image guided percutaneous biopsy is observed in 3%-16% of cases, which may arise with inadequate sampling, and raises risks of false negative diagnosis, particularly in well differentiated HCC. The chances of success with repeat biopsy is relatively low when the deficiency is limited by characteristics of the lesions, such as areas of necrosis in large nodules or well differentiated cellular areas in small sized HCC, and increases the risk of bleeding and tumor seeding (42).…”
Section: The Role Of Liver Biopsymentioning
confidence: 99%
“…The incidence of seeding has been the subject of a number of studies, with reported incidence varying widely from 0 to 11%. [53][54][55][56][57][58] A literature review performed by Stigliano et al 55 concluded that the overall mean risk of seeding is 1.73%, based on results from 2242 patients. The exact incidence of needle tract seeding is difficult to accurately determine, as there have been only case reports and small retrospective studies.…”
Section: Post-fine-needle Aspiration Soft-tissue Metastasesmentioning
confidence: 99%